2021
DOI: 10.1002/wat2.1519
|View full text |Cite
|
Sign up to set email alerts
|

Updating intensity–duration–frequency curves for urban infrastructure design under a changing environment

Abstract: The intensity and frequency of extreme precipitation have increased in many regions in the past century due to climate change. Many studies have revealed that short‐duration extreme precipitations are likely to become more and more severe in many areas, thus raising a question on whether our urban infrastructures have been designed adequately to cope with these changes. Currently, Intensity–duration–frequency (IDF) curves, which summarize the relationships between the intensity and frequency of extreme precipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 140 publications
0
23
0
Order By: Relevance
“…In future studies, we plan to include spatial covariates into the estimation of the newly proposed d-GEV parameters, including intensity offset, in order to use data from different locations more efficiently. Also, the concept of non-stationary precipitation with respect to IDF curves is important to consider (see Cheng and AghaKouchak, 2014;Ganguli and Coulibaly, 2017;Yan et al, 2021) since extremes are expected to vary due to climate change. For example, Benestad et al (2021) found a model that enables downscaling of 24 h measurement data to shorter durations without assuming stationarity.…”
Section: Discussionmentioning
confidence: 99%
“…In future studies, we plan to include spatial covariates into the estimation of the newly proposed d-GEV parameters, including intensity offset, in order to use data from different locations more efficiently. Also, the concept of non-stationary precipitation with respect to IDF curves is important to consider (see Cheng and AghaKouchak, 2014;Ganguli and Coulibaly, 2017;Yan et al, 2021) since extremes are expected to vary due to climate change. For example, Benestad et al (2021) found a model that enables downscaling of 24 h measurement data to shorter durations without assuming stationarity.…”
Section: Discussionmentioning
confidence: 99%
“…We can affirm that most existing stormwater runoff infrastructures are ill-adapted, and design strategies, including climate change adaptation, need to be implemented (Lopez-Cantu and Samaras 2018;Myhre et al 2019). IDF curves are a critical part of the design process and require updating to account for an evolving climate and reduce infrastructure vulnerability (ASCE 2018;Watt and Marsalek 2013;Yan et al 2021).…”
Section: Introductionmentioning
confidence: 98%
“…It is now recognized that these changes are responsible for higher frequency and/or intensity of extreme rainfall (Ganguli and Coulibaly, 2017;Agilan and Umamahesh, 2016). Rainfall extremes and their statistical properties are important for proper estimations of design values in numerous engineering infrastructures such as urban drainage systems, bridges, railways, highways, rain harvesting systems and road culverts can be designed more economically when the frequency of extreme rainfall is known (Yan et al, 2021;Lakatos et al, 2020;Onderka et al, 2020;Bara et al, 2009;Faško et al, 2000). Rainfall extremes can studied at a range of spatial and temporal scales (AghaKouchak et al, 2013;Diffenbaugh and Giorgi, 2012;Jakob, 2013;Kharin et al, 2007).…”
Section: Introductionmentioning
confidence: 99%